Association of Serum Thyroid Hormone Levels with Androgen and Metabolic Parameters in Chinese Women with Polycystic Ovary Syndrome: A Retrospective Cross-Sectional Study - Manman Pan; Jinghua Zhang; Qing Zhang; Fangfang Wang; Fan Qu; Mei Jin (Clinical and Experimental Obstetrics & Gynecology)
Background: We sought to explore the potential relationship between serum levels of thyroid hormones with those of androgen and metabolic parameters in women with polycystic ovary syndrome (PCOS). Methods: Data from 1059 Chinese women with PCOS and 1015 healthy women was retrospectively collected. This data including fasting glucose and insulin, thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), free thyroxine (FT4), total triiodothyronine (TT3), total thyroxine (TT4), anti-thyroperoxidase antibody (ANTI-TPO), anti-thyroglobulin (ATG), dehydroepiandrosterone sulfate (DHEAS), total testosterone (TTE), follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), prolactin (PRL), progesterone (PGN), triglyceride (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL) and low-density lipoprotein cholesterol (LDL). Thyroid-related indicators were compared between PCOS and non-PCOS patients enrolled in this study. Independent variables of PCOS were compared among subgroups in accordance with the classification of TSH, homeostatic model assessment of insulin resistance (HOMA-IR), and TTE levels. To further explore the association between thyroid hormones levels and correlated metabolic parameters in PCOS, multiple regression analyses were conducted. Results: Our study found that PCOS patients had significantly higher serum TSH, FT3, TT3 and TT4 levels than non-PCOS patients. PCOS patients with TSH ≥2.5 mIU/L had significantly higher TG, fasting insulin, HOMA-IR and homeostatic model assessment of β-cell function (HOMA-B), however, these patients also displayed significantly lower DHEAS, HDL, and quantitative insulin sensitivity check index (QUICKI) when compared to patients with TSH levels <2.5 mIU/L. PCOS patients with HOMA-IR levels ≥2.5 mIU/L demonstrated significantly higher FT3 and TSH, but lower TT3 when compared to women with HOMA-IR levels <2.5 mIU/L. Four groups divided by TTE displayed significant differences in FT3 in PCOS patients. Multiple linear regression analysis showed that TSH was significantly negatively associated with DHEAS and QUICKI. Conclusions: TSH levels are closely correlated to the metabolic and endocrine characteristics of PCOS, especially dyslipidemia and insulin resistance.